2012
DOI: 10.1167/iovs.11-8732
|View full text |Cite
|
Sign up to set email alerts
|

Transsynaptic Retinal Degeneration in Optic Neuropathies: Optical Coherence Tomography Study

Abstract: PURPOSE.Recently demonstrated neuronal loss in the inner nuclear layer of the retina in multiple sclerosis (MS) and glaucoma raises the question of a primary (possibly immune-mediated) or secondary (transsynaptic) mechanism of retinal damage in these diseases. In the present study we used optical coherence tomography to investigate retrograde retinal transsynaptic degeneration in patients with long-standing and severe loss of ganglion cells due to optic neuropathy. METHODS. Fifteen eyes of glaucoma patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 31 publications
4
27
0
1
Order By: Relevance
“…Similar to the findings observed in global study cohorts of patients with CIS,4 17 18 the thickness of the GCL/IPL layer was found to be significantly thinner in ON+ versus ON− eyes (Mann–Whitney U test, p<0.001). The INL, ONL-IS and OS-RPE thicknesses were, however, thicker in ON+ eyes compared with ON− eyes (Mann–Whitney U test, p<0.001; p<0.01 and p<0.05, respectively) (figure 3A).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to the findings observed in global study cohorts of patients with CIS,4 17 18 the thickness of the GCL/IPL layer was found to be significantly thinner in ON+ versus ON− eyes (Mann–Whitney U test, p<0.001). The INL, ONL-IS and OS-RPE thicknesses were, however, thicker in ON+ eyes compared with ON− eyes (Mann–Whitney U test, p<0.001; p<0.01 and p<0.05, respectively) (figure 3A).…”
Section: Resultssupporting
confidence: 84%
“…In line with these findings, thinning of the RNFL and the GCL/IPL after ON has been demonstrated previously4 8 17 19–21 and was observed not only in MS but also in patients with CIS,4 17 suggesting that it is a direct consequence of ON. It also persists over time following the ON episode 20 21.…”
Section: Discussionsupporting
confidence: 88%
“…A more speculative explanation is trans-synaptic retrograde degeneration, a phenomenon controversially discussed for decades [31][32][33][34][35][36][37][38][39][40], induced by optic radiation damage causing retinal thinning detectable by OCT. In our study, the association between focal tissue destruction in the OR and thinning of the RNFL remained significant even when considering exclusively patients without a history of ON, indicating that retinal axonal degeneration in MS occurs partially independent of ON -a notion also supported by previous OCT studies [14][15][16]41].…”
Section: Discussionmentioning
confidence: 99%
“…Of the in vivo studies using OCT, only Saidha et al reported thinning of the INL and OPL in a subgroup of MS eyes without MSON and suggested this thinning was the results of a primary retinal process [69]. On the other hand, several other studies reported no thinning, or preservation of the INL [51,70,71].…”
Section: Trans-synaptic Axonal Degenerationmentioning
confidence: 99%